2018
DOI: 10.1093/mnras/sty2740
|View full text |Cite
|
Sign up to set email alerts
|

The 21-cm bispectrum as a probe of non-Gaussianities due to X-ray heating

Abstract: We present analysis of the normalised 21-cm bispectrum from fully-numerical simulations of intergalactic-medium heating by stellar sources and high-mass X-ray binaries (HMXB) during the cosmic dawn. Lyman-α coupling is assumed to be saturated, we therefore probe the nature of non-Gaussianities produced by X-ray heating processes. We find the evolution of the normalised bispectrum to be very different from that of the power spectrum. It exhibits a turnover whose peak moves from large to small scales with decrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 74 publications
4
74
0
Order By: Relevance
“…Ref. [52] indeed confirmed that there is a clear effect present in the measurements of the bispectrum. How about observational prospects of the response functions?…”
Section: Summary and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Ref. [52] indeed confirmed that there is a clear effect present in the measurements of the bispectrum. How about observational prospects of the response functions?…”
Section: Summary and Discussionmentioning
confidence: 66%
“…Ref. [52] have carried out a theoretical study of detectability of the bispectrum in SKA-Low observations in the presence of telescope noise. They find that for 1000-hour integration time the bispectrum from the equilateral triangle configuration will be detectable.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This result further motivates the use of alternative analysis techniques to interpret the signal from the CD to probe for rare X-ray sources. The bispectra of the 21-cm signals from all the X-ray simulations presented here have been extensively studied in Watkinson et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is compensated for by having a wider range of baselines, meaning a fuller interferometric U-V coverage. Despite this SKA does not achieve tighter posterior contours on parameters, when considering the power spectrum -this might not remain the case when considering higher order statistics such as the bispectrum (Watkinson et al 2019). For a direct comparison of HERA-331 and SKA's observational error on the power spectrum see Figure 4.…”
Section: Varying the Number Of Hera Dipolesmentioning
confidence: 99%